Blocking proteinase-activated receptor 2 alleviated neuropathic pain evoked by spinal cord injury - Wei, H; Wei, Y; Tian, F; Niu, T; Yi, G (Physiological research, 2016)
Spinal cord injury (SCI) is an extremely serious type of physical trauma observed in clinics. Especially, neuropathic pain resulting from SCI has a lasting and significant impact on most aspects of daily life. Thus, a better understanding of the molecular pathways responsible for the cause of neuropathic pain observed in SCI is important to develop effectively therapeutic agents and treatment strategies. Proteinase-activated receptors (PARs) are a family member of G-protein-coupled receptors and are activated by a proteolytic mechanism. One of its subtypes PAR2 has been reported to be engaged in mechanical and thermal hyperalgesia. Thus, in this study we specifically examined the underlying mechanisms responsible for SCI evoked-neuropathic pain in a rat model. Overall, we demonstrated that SCI increases PAR2 and its downstream pathways TRPV1 and TRPA1 expression in the superficial dorsal horn of the spinal cord. Also, we showed that blocking spinal PAR2 by intrathecal injection of FSLLRY-NH2 significantly inhibits neuropathic pain responses induced by mechanical and thermal stimulation whereas FSLLRY-NH2 decreases the protein expression of TRPV1 and TRPA1 as well as the levels of substance P and calcitonin gene-related peptide. Results of this study have important implications, i.e. targeting one or more of these signaling molecules involved in activation of PAR2 and TRPV1/TRPA1 evoked by SCI may present new opportunities for treatment and management of neuropathic pain often observed in patients with SCI.
Keywords: receptor PAR-2; cinnamáty; poranění míchy; Oligopeptides; Purines; Anilides; krysa rodu Rattus; Spinal Cord Injuries; zvířata; acetanilidy; oligopeptidy; potkani Wistar; neuralgie; Cinnamates; Neuralgia; Acetanilides; Rats, Wistar; Male; puriny; Receptor, PAR-2; Rats; Animals; mužské pohlaví; anilidy; spinální injekce; Injections, Spinal